Desenvolvimento de um dashboard aplicando Self-Service Business Intelligence e conceitos de User Experience - Nering, Eduardo Schneider (2022)
In search for competitive advantage, a lot of companies are considering how to take their decisions in a more intelligent and data-driven way. The industry 4.0 has revolutionized not only production processes, but also the companies’ culture. This change associated with the emerging availability of data results in the possibility of Business Intelligence (BI) tools implementation, that by gathering and transforming data enables a more assertive decision-making. This process starts to evolve and share space with the implementation of more lean solutions, such as Self-Service Business Intelligence (SSBI). It surges to overcome the increasing demands for more accessible tools and user empowerment, leading to more agile analysis. The current work has the objective of developing a dashboard applying the concepts of SSBI by using the Power BI software. The data used as source were from a Supply Chain sector of an oil and gas company, with the goal of supporting the internal process of risk management for suppliers’ deliveries. Also looking for empowering the dashboard users and improving their use of the tool, the development was made with concepts of User Experience (UX), set of elements and factors related to the interaction of an user with a system, product or service. After rounds of feedback, it was possible to improve the visualizations with the user’s perception of the presented information. The result was an interactive and visually optimized dashboard, containing two pages for the view from two teams. The main visual developed started as a scatter chart and progressed to a supplier’s risk matrix, by the application of multiple data visualization improvement concepts, supported by the construction of measures in DAX language. The model highlighted the capability of SSBI of enabling the development of multifaced analysis, that can be improved the higher knowledge acquired of the process and tool.